2017
DOI: 10.1038/mi.2016.116
|View full text |Cite
|
Sign up to set email alerts
|

The loss of CCR6+ and CD161+ CD4+ T-cell homeostasis contributes to disease progression in SIV-infected rhesus macaques

Abstract: While previous studies have shown that CD4+ T cells expressing CCR6 and CD161 are depleted from blood during HIV infection, the mechanisms underlying their loss remain unclear. In this study, we investigated how the homeostasis of CCR6+ and CD161+ CD4+ T cells contributes to SIV disease progression and the mechanisms responsible for their loss from circulation. By comparing SIV infection in rhesus macaques (RMs) and natural host sooty mangabeys (SMs), we found that the loss of CCR6+ and CD161+ CD4+ T cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 70 publications
(111 reference statements)
7
41
0
Order By: Relevance
“…These two reports (86,87) further support the conclusions of our current study, which reveals the key role played by mTOR in regulating multiple postentry and postintegration HIV replication steps in gut-homing Th17-polarized CCR6 + T cells. In conclusion, our findings point to CCR6 as a "zip code" molecule expressed on the surface of CD4 + T cells transcriptionally programmed to become HIV targets upon recruitment into the intestine and provide a detailed molecular explanation for preferential HIV/SIV replication and persistence in gut-homing CCR6 + CD4 + T cells (24,25,37,42). Most significantly, we reveal the role of the mTOR pathway in regulating effector functions as well as HIV permissiveness in gut-homing CCR6 + Th17 cells at multiple postentry levels.…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 99%
See 1 more Smart Citation
“…These two reports (86,87) further support the conclusions of our current study, which reveals the key role played by mTOR in regulating multiple postentry and postintegration HIV replication steps in gut-homing Th17-polarized CCR6 + T cells. In conclusion, our findings point to CCR6 as a "zip code" molecule expressed on the surface of CD4 + T cells transcriptionally programmed to become HIV targets upon recruitment into the intestine and provide a detailed molecular explanation for preferential HIV/SIV replication and persistence in gut-homing CCR6 + CD4 + T cells (24,25,37,42). Most significantly, we reveal the role of the mTOR pathway in regulating effector functions as well as HIV permissiveness in gut-homing CCR6 + Th17 cells at multiple postentry levels.…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 99%
“…Most recently, CD4 + T cells expressing the Th17 markers CCR6 and RORγt were identified as the first targets of SIV during vaginal transmission (24); in addition, the detrimental role of viral permissive CCR6 + T cell infiltration into the gut was documented (25). The depletion of Th17 cells from the GALT upon HIV infection persists despite viral-suppressive ART (26)(27)(28), even when ART is intensified with integrase and CCR5 inhibitors (29).…”
Section: Introductionmentioning
confidence: 99%
“…During the 60-day observation period, peripheral blood mononuclear cells (PBMCs) were collected at four time points. Colorectal mucosal lamina propria mononuclear cells (LPMCs) were biopsied by using an endoscope four times before or after PBMCs collection for the sake of animal welfare (McGary et al, 2017). Rectal fluid was collected at eight time points.…”
Section: Animal Model and Longitudinal Tracingmentioning
confidence: 99%
“…Mavigner and colleagues in 2012 demonstrated that T‐helper cells expressing the gut homing receptor CCR9 accumulate in the bloodstream of HIV‐infected individuals under ART, and proposed that the reduced expression of CCR9 agonist, CCL25, in the intestine prevents a proper recruitment of these cells into the tissues . On the contrary, is still debated if expression of CCL20 and CXCL10 is maintained or reduced in the intestine during the infection, probably due to the fact that the intestinal mucosa of different anatomical sites have been analyzed by the different groups. Recently, we have shown that T‐helper cells expressing the chemokine receptor CCR6 and CXCR3 accumulate in the blood of ART treated HIV‐1 infected patients and that their frequency correlates with markers of chronic immune activation .…”
Section: Modulation Of Chemokine Activity During Hiv‐1 Infectionmentioning
confidence: 99%
“…In HIV-1 infection, chemokine receptors are used as co-receptor for viral entry, the virus hijacks the cytoskeleton machinery to favor integration in the host genome, 67 in the intestine prevents a proper recruitment of these cells into the tissues. 82 On the contrary, is still debated if expression of CCL20 and CXCL10 is maintained or reduced in the intestine during the infection, 66,83,84 probably due to the fact that the intestinal mucosa of Recently, we have shown that T-helper cells expressing the chemokine receptor CCR6 and CXCR3 accumulate in the blood of ART treated HIV-1 infected patients and that their frequency correlates with markers of chronic immune activation. 66 Noteworthy, these cells express normal levels of chemokine receptors, but are not able to migrate in response to chemokines.…”
Section: Modulation Of Chemokine Activity During Hiv-1 Infectionmentioning
confidence: 99%